ANALISIS PREFERENSI KONSUMEN SIM CARD PRABAYAR DI KOTA TANJUNG REDEB - Asmawati, Asmawati (CAM JOURNAL, Jurnal Agen Perubahan Manajemen, 2017)
This study aims to: a) analyze consumer preference towards prepaid sim card based on the component of interest, b) to analyze consumer preferences for pre-paid sim card based on the belief component, and c) to analyze consumer attitudes towards pre-paid sim card.The analytical method used is the Fishbein Multiattribute Attitude Model. The research results show that 1) the attribute signals, extensive networking, and voice clarity with a very important category. Sms rates, cheap phone rates, years of grace period is active with important categories. Voucher price, the price and the promotion with moderate category. 2) Simpati sim card on signal attributes, network wide, clarity of voice and SMS tariffs ranked first, second, third and fourth with a strong believer category. Cheap phone rates, prime rates, grace periods with confidence category. Voucher prices and promotions ranked eighth and ninth with a middle category. Mentari sim card shows that the attributes of the signal, occupies the first position with a strong believer category. clarity of voice, broad network, sms rates, cheap phone rates, grace periods and active position with the categories in disbelief. Initial price, promotion with moderate category. (3) Fishbein attitude model established by the Consumer to the sim card with a total of 155.60 Simpati good attitude category. While the sim card with a 137.50 total Mentari acquire Ordinary attitude category.